PROJECT IMPLEMENTATION STRATEGY AND PERFORMANCE OF OIL AND GAS FUNDED PROJECTS IN NIGER DELTA REGION OF SOUTH SOUTH, NIGERIA - Adedapo, Giwa, Emmanuel; Emenike, Augusta Ifeoma; Okafor, Ozoemena Christian; Ezea, Chinonyelum Nneoma (International Journal of Allied Research in Economics (IJARE), 2023)
The researcher aimed to examine the relationship between project implementation strategy and the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria. The specific objectives are as follows: to assess the extent of the relationship between project design and the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria, and to determine the extent of the relationship between project monitoring and the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria. The researcher adopted a survey research design. The total population of the study was 1,272,000, drawn from two selected local government areas in Delta State, namely Warri and Burutu. The sample size for the study was 400, determined using Taro Yamane’s statistical formula. Spearman’s rank correlation method was employed to test hypotheses. The findings indicated that project design had a significant positive relationship with the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria (r=0.458, p<0.05), and project monitoring had a significant positive relationship with the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria (r=0.457, p<0.05). The study concluded that project implementation strategy has a significant positive relationship with the performance of oil and gas-funded projects in the Niger Delta Region of South-South, Nigeria. Based on the findings, the study recommends that contractors responsible for oil and gas-funded projects should prioritize the identification of key elements necessary for designing and monitoring projects to benefit the government and stakeholders in the communities. in teaching the students